HIPERTROFIA MAMÁRIA: Estudo comparativo entre os achados por exames de imagem e histopatológico. - Mocelin, Paulo Roberto (2008)
Introduction: The breast is an important female and sexually symbol. The presence of hypertrophy and affections in this organ generate effects of psychosocial order. The breast hypertrophy ,even though cause problems of physical and psychological orders, may difficult detection of alterations in the image exams (ultrasonography and mammography) because of its volume. Objectives: To evaluate sensibility and specificity of mammography and ultrasonography on the detection of breast alterations in patients with breast hypertrophy in many degrees. Material and Methods: Prospective study realized in 60 patients with breast hypertrophy in the plastic surgery service from Federal University of Maranhão Hospital, in the period of april 2005 to october 2006. It was made a correlation between the image exams with hystopathological exams, golden standard, of the 120 surgery pieces obtained with the breast reduction plastic surgery. Results: The group age studied was 16 to 72 years and the breasts that weighted until 800g corresponded 65% of all the cases.On the images exams, BI-RADS 1was the most frequent (65,8% on the ultrasonography and 26,7% on the mammography).About the histopathology was diagnosticated 47,5% of non benign neoplasias lesions with 7,5% of a discrete increase on its relative risk. Conclusions: On the ultrasonography, specificity didn´t presented variations according to the literature. Although ultrasonography sensibility presented compromised the hypertrophy. The specificity of mammography was low on the population studied and the sensibility, independent of the age, presented compatible results with dense breasts. To the population studied, mammography was deficient to detect alterations diagnosed on the histopathology.